Repairing of Heavily Cracked Unbonded Post-Tensioned Structural Systems (International Journal of Innovative Research in Engineering & Management, 2022)
Reinforced concrete moment resisting  frames (RCMRF) are structural systems that should be  designed to ensure proper energy dissipation capacity  when subjected to seismic loading. In this design  philosophy the capacity design approach that is currently  used in practice demands “strong-column / weak-beam”  design to have good ductility and a preferable collapse  mechanism in the structure. When only the flexural  strength of longitudinal beams controls the overall  response of a structure, RC beam-column connections  display ductile behavior (with the joint panel region  essentially remaining elastic). The failure mode where in  the beams form hinges is usually considered to be the most  favorable mode for ensuring good global energy dissipation without much degradation of capacity at the  connections. Though many international codes  recommend the moment capacity ratio at beam column  joint to be more than one, still there are lots of  discrepancies among these codes and Indian standard is  silent on this aspect.
Keywords: Linear & Non-Linear analysis; RCC & Precast beam-column connections; Seismic; Prestressed Ground Motion; Panel building